(untitled) (Journal of Information Technology and Digital World, 2021)
The main aim of this project is to develop a Graphical User Interface (GUI) based system to monitor and control the industrial process. The proposed protocol os user-friendly and it is more efficient due to the incorporation of a simple GUI. Moreover, the proposed system is installed to collect the valuable information.